Aktivitas Fisik dengan Intensitas yang Sering Dapat Meningkatkan Kecerdasan Emosional pada Remaja: Physical Activity with Frequent Intensity Can Increase Emotional Intelligence in Adolescents - Evi Tri Wahyuni; Yeni Koto; Indri Sarwili (Dohara POAJ, 2021)
Introduction: Physical activity or sport is one way to achieve physical health. The activities carried out are beneficial not only physically but mentally, emotionally, and spiritually. Teenagers have a large enough population emotional intelligence is very useful for negative energy that comes to teenagers. Methods: The method used is quantitative research using cross sectional design. With 67 respondents, the sampling technique used the Slovin formula. Using the Spearman Rank test statistical test. The instrument used was a questionnaire. Results: From the results of the research conducted there were 39 respondents (58.2%) who did heavy physical activity, 28 respondents (41.8%) who did light physical activity. Meanwhile, there were 38 respondents (56.7%) who had high emotional intelligence and 29 respondents (43.3%) had low emotional intelligence. From the results of the Spearman Rank statistical test conducted by the researcher, it was found that N = 67, with a correlation of 0.848 with a P value of 0.000. Discussion: The conclusion of this study is that it has a very strong meaning so that Ho is denied. Ha is accepted, it’s means there is a connection between physical activity variables and emotional intelligence, and the direction of the relationship between the two variables is positive.